Scrutinizing the Emotional Nature of Intuitive Coherence Judgments - Zander, Thea (J Behav Decis Mak, 2016)
Dual‐system models propose that cognitive processing can occur either intuitively or deliberately. Unlike deliberate decision strategies, intuitive ones are assumed to have an emotional component attached to the decision process. We tested if intuitive decisions are indeed accompanied by an emotional response while deliberate decisions are not. Specifically, we conducted a psychophysiological study in which participants were instructed to decide either intuitively or deliberately if three simultaneously presented words were semantically coherent or incoherent (triad task). The degree of emotionality of these two decision strategies (intuitive vs. deliberate) was compared using changes in electrodermal activity (EDA) and the reaction time (RT) effect of an affective priming paradigm as primary measurements. Based on a valence‐arousal model, our results revealed that intuitive and deliberate judgments do not differ as to their emotional valence but that they do differ in emotional arousal. Most notably, sympathetic activation during intuitive judgments was significantly lower compared to sympathetic activation during deliberate judgments. Our results reflect that a relaxed state of mind—manifested in low sympathetic activity—could underlie the holistic processing that is assumed to facilitate the proliferation of semantic associations during coherence judgments. This suggests that coherence judgments made under an (instructed) intuitive decision mode have a specific psychophysiological signature and that arousal is the differentiating component between intuitive and deliberate decision strategies. © 2016 The Authors Journal of Behavioral Decision Making Published by John Wiley & Sons Ltd.